KEMAMPUAN MENULIS PUISI ANAK PADA SISWA KELAS V SD INPRES MALLENGKERI I KOTA MAKASSAR - Alfina Pratiwi.N; Andi Paida; Ratnawati (Almeera Education, 2023)
The aim of the study was to identify the ability to write children's poetry in fifth-grade students at SD Inpres Mallengkeri I Makassar City. This type of research is descriptive qualitative. The data collection techniques used in this study were observation, interviews, and documentation, while the instruments I used were observation guidelines, interview guidelines, and documentation. Based on the results of data analysis using descriptive qualitative analysis, it was stated that the ability to write poetry for fifth-grade students at SD Inpres Mallengkeri I, Makassar City obtained good results but still needs to be trained. Obstacles in writing children's poetry and how to overcome them in class V students at SD Inpres Mallengkeri I Makassar City, namely especially in writing spelling as well as the relationship between one paragraph and another paragraph, limited by the time given by the teacher so that students are unable to think quietly. The way to overcome this is that they are often given more practice and given special guidance in writing or repeated writing and given directions and explanations about using good spelling.